RORα Regulates Odontoblastic Differentiation and Mediates the Pro-Odontogenic Effect of Melatonin on Dental Papilla Cells - Jun Kang; Haoling Chen; Fuping Zhang; Tong Yan; Wenguo Fan; Liulin Jiang; Hongwen He; Fang Huang (Molecules, 2021)
Dental papilla cells (DPCs), precursors of odontoblasts, are considered promising seed cells for tissue engineering. Emerging evidence suggests that melatonin promotes odontoblastic differentiation of DPCs and affects tooth development, although the precise mechanisms remain unknown. Retinoid acid receptor-related orphan receptor α (RORα) is a nuclear receptor for melatonin that plays a critical role in cell differentiation and embryonic development. This study aimed to explore the role of RORα in odontoblastic differentiation and determine whether melatonin exerts its pro-odontogenic effect via RORα. Herein, we observed that RORα was expressed in DPCs and was significantly increased during odontoblastic differentiation in vitro and in vivo. The overexpression of RORα upregulated the expression of odontogenic markers, alkaline phosphatase (ALP) activity and mineralized nodules formation (p < 0.05). In contrast, odontoblastic differentiation of DPCs was suppressed by RORα knockdown. Moreover, we found that melatonin elevated the expression of odontogenic markers, which was accompanied by the upregulation of RORα (p < 0.001). Utilising small interfering RNA, we further demonstrated that RORα inhibition attenuated melatonin-induced odontogenic gene expression, ALP activity and matrix mineralisation (p < 0.01). Collectively, these results provide the first evidence that RORα can promote odontoblastic differentiation of DPCs and mediate the pro-odontogenic effect of melatonin.